Structural health monitoring of turbo generator foundation - Fatemeh Sharafi; Reza Karami Mohammadi (Numerical Methods in Civil Engineering)
Structural health monitoring has been widely used during the past decades to evaluate the safety of structural assets, detect damages at an early stage, and prevent unexpected and costly damages. The research works in this field are often concerned with bridges and buildings and little research has been conducted on structural health monitoring of power plant infrastructures such as machine foundations. The turbo generator, also referred to as the heart of the power plant, is supported by massive concrete foundations in the turbine hall of thermal power plants. Most TG foundations in thermal power plants are at or close to their design age. The reports on structural damages in thermal power plants show that cracks are frequently observed on the beams and columns of frame-type TG foundations. It is probably the most appropriate time for developing vigorous methods for health monitoring of power plant structures to extend their reliability and life span. This paper uses the vibration-based approach for damage detection of TG foundations. Analytical mode decomposition (AMD) and experimental mode decomposition (EMD) methods are both used for modal parameter identification. A genetic algorithm is further used for finite element model updating and damage detection. The performance of the method is investigated using a 3-D finite element model of a frame-type TG foundation.